Surveillance, breeding, and cultural practices to prevent a rust storm on crops and trees. (13th December 2021) - Brar, Gurcharn S.; Feau, Nicolas; Gill, Upinder S.; Hiebert, Colin; Leboldus, Jared; Park, Robert F.
Abstract: The rust fungi (Pucciniales) are among the most common and devastating pathogens of field crops and forest tree species worldwide. Given the importance of the rusts in agriculture and forestry, this Special Issue of the Canadian Journal of Plant Pathology brings together a variety of papers on rust disease management and biology. The Special Issue comprises 16 full-length articles on rust pathogens of field crops and white pine. Two are review articles summarizing recent advances in rust pathology, two are first reports of new pathogens/diseases in new geographical territories, and 12 articles present results that advance knowledge of rust pathogens in the areas of pathogen population biology, host—pathogen interactions, and resistance breeding. We trust that the articles assembled in this Special Issue will highlight the power of virulence phenotyping coupled with genetic mapping for building durable rust resistance in staple crops such as wheat, as well as the ongoing need for research on rust fungi in field crops and forest trees.